A model for fracture of temperature-sensitive hydrogel with diffusion and large deformation - Zheng, Shoujing (2023)
A model is formulated theoretically in this paper via the phase field method for simulation of fracture in temperature-sensitive hydrogels with consideration of diffusion coupled with large deformation, based on the finite-element analysis with analogies between the phase field evolution law and heat transfer as well as between the diffusion law and heat transfer. The model is implemented by the commercial finite-element code ABAQUS/Standard, through its in-built features to robustly simulate the 2D or 3D fracture process under various boundary conditions for the smart hydrogels at both equilibrium and transient states. In particular, no preset crack is required by the model with capability to simulate of the fracture for different types of temperature-sensitive hydrogels under various boundary conditions. Subsequently, the model is validated by comparison with the experimental fracture data of temperature-sensitive hydrogel published in open literature. After that, several parameter studies are carried out numerically to demonstrate the robustness of the model and to understand the influence of temperature and diffusion on the fracture process of the hydrogels. Finally, three case studies of fracture occurring in potential engineering are investigated. The provided source codes and the tutorials make it easy for practicing engineers and scientists to model crack propagation in soft gel materials.